Electrocaloric effect in Ba0.2Ca0.8Ti0.95Ge0.05O3 determined by a new pyroelectric method. (28th September 2015) - Asbani, B.; Dellis, J.-L.; Gagou, Y.; Kaddoussi, H.; Lahmar, A.; Amjoud, M.; Mezzane, D.; Kutnjak, Z.; El Marssi, M.
Abstract: The present letter explores the electrocaloric effect (ECE) in the lead-free oxide Ba0.8 Ca0.2 Ti0.95 Ge0.05 O3 ceramics (BCTG). The electrocaloric responsivity was determined by two different methods using the Maxwell relationship . In a first well-known indirect method, hysteresis loops were measured in a wide temperature range from which the pyroelectric coefficient and thus ξ were determined by derivation of data. In the second novel method the pyroelectric coefficient p E and consequently the electrocaloric responsivity ξ were determined by direct measurements of the pyroelectric currents under different applied electric fields. Within the experimental error, good agreement was obtained between two methods with at about 410 K.